Economic valuation of household preference for solid waste management in Malaysia: A choice modeling approach - Othman, Jamal (Universiti Utara Malaysia, 2007)
This study estimated the economic values of household preferences for improved solid waste management (SWM) service attributes in Malaysia. The Choice Model (CM) was employed on 859 randomly selected urban households in Kajang and Seremban areas. The study found that households were willing to pay a premium for improvements in the SWM system. More specifically, the study ascertains that households on average are willing to pay a charge of RM1.57 per month for a change in collection frequency - from 3 irregular times to either 3 scheduled times or 4 times per week, ceteris paribus; RM3.32 if waste disposal method was improved from control tipping to sanitary landfill, ceteris paribus; and RM2.48 if transportation mode was improved from a mix of compactor and open trucks to either compactor or a mix of compactor and covered trucks, ceteris paribus. The CM has also shown that households derive positive utility from the provisions of recycling facilities and compulsory kerbside recycling with an implicit price (willingness to pay) of about RM3.51 monthly. Results from the study can be used by service providers to identify any mismatch between what the public actually wants and are willing to pay for and the affordability of supply on the part of service providers.